Methods and applications of statistics in the atmospheric and earth sciences - Balakrishnan, N., 1956- (Hoboken, New Jersey : Wiley, 2013)
"Provides a realistic alternative to the individual user who would like a quick reference containing encyclopedic information that pertains to their particular research interests and needs"--